Following suit - Y. Wang; Z. Shi; H. Li; F. Fei (Grounded Theory Review: An International Journal, 2023)
Given the rapid surge in the number of studies claiming the adoption and use of the grounded theory (GT) methodology in China over the past two decades or so, we can now confirm that virtually all studies haven’t been at all conducted in accordance with the GT methodology including its variants, let alone the classic one extended by Glaser and Strauss (1967). We are fascinated by the behaviours of those who have chosen to remodel the original GT methodology (Glaser, 2003), a pattern of which is ascertained as “following suit.” It explains the solution finding process in relation to their central concern of having their work legitimised. Three overlapping and yet, distinctive sub-dimensions of “following suit” have also been identified, which are named as “fitting-in,” “window-dressing,” and “pretexting”. The notion of “following suit” has its general implications elsewhere and in other methods too, as we have also noticed. And we are alert to the probability that some may use the criterion of “modifiability” of GT (Glaser, 1978) as a pretext of remodelling the GT methodology in the pursuit of their own agendas.